Acremonium sclerotigenum‐Acremonium egyptiacum: a multi‐resistant fungal pathogen complicating the course of aplastic anaemia. (30th August 2013) - Guitard, J.; Degulys, A.; Buot, G.; Aline‐Fardin, A.; Dannaoui, E.; Rio, B.; Marie, J. P.; Lapusan, S.; Hennequin, C.; Drancourt, M.
Abstract A patient with aplastic anaemia, successively treated with caspofungin then liposomal amphotericin, developed a disseminated infection due to Acremonium, further confirmed as resistant in vitro to these drugs. Successful treatment was achieved with voriconazole. Multiple antifungal treatments may expose to the risk of breakthrough of multi‐resistant pathogens in haematology patients.